Digitalization and Luxury : The Role of Digital Experience and Online Content on Purchasing Intention of Luxury Goods - Veseľková, Nikoleta (2023)
The primary objective of this diploma thesis is to identify key factors that affect purchase intention for personal luxury, with emphasis on the role of the digital experience and online content. The work is divided into three main chapters. The first chapter is devoted to the specificities of the luxury industry, the luxury market overview and its current challenges and trends. The following chapter captures the relationship between digitalization and luxury by focusing on luxury marketing in the digital world, characterizing the luxury clients, their luxury purchases and examining pre-purchase phase of their digital journey. The third chapter, primary research, describes in detail the whole process and steps applied in the elaboration of the questionnaire. Besides, it analyzes and summarizes the gathered quantitative data. The research identifies the intrinsic motivation, the Perfectionism effect, as motivation driving the purchase intention for personal luxury with different factors affecting online and offline shopping. Lastly, it summarizes the role of digital experience and online content in the pre-purchase phase on websites, applications, social networks, metaverse or generated through bloggers and influencers as convincing, promoting, impacting buying decisions, entertaining, educating and inspirational for personal luxury customers. These findings can be further utilized in the marketing strategies of luxury fashion brands.